O riso em Mainardi: um estudo sobre os mecanismos linguístico-discursivos do humor nas crônicas de Diogo Mainardi - Silva, Sandra Falcão da (2009)
This study aims at identifying and analyzing the linguistic and discursive mechanisms in the humorous discourse in Diogo Mainardi chronicles. Fifteen chronicles from Veja magazine (2005-2008) have been selected for a corpus to develop this research. Some of them appear in the book Lula é minha Anta (2007). Regarding our object, the discursive strategies related to humor have been highlighted in the chronicler s texts with the purpose of inferring the possible effects with social sense upon their potential readers. A discursive approach of the language has been employed. This study has started out with a theoretical reference based on Discourse Analysis theories in the media context. Considering the objective of this work, reference thinkers on humor and more specifically on irony have been contemplated as well. The necessary theoretical support has been extracted from these theories for the examination of the features that made the humor particular, and especially, in our adopted discourse conception aiming at understanding the discursive functions of humor in Mainardi chronicles. The research material analysis has revealed that the social sense of the humorous act depends on an adhesion contract proposed by the speaker-enunciator to the interlocutor that demands an interactive work on the construction of text meaning based on shared knowledge. Intertextuality and interdiscourse so provide the humorous act that point at some such socialdiscursive imaginariness commonly found in the protagonists. All things considered, the linguistic and discursive mechanisms related to the humour, highlighted in Mainardi s chronicles, proved it to be an evident strategy, due to its controversial nature, to convince the reader and get his/her support with the purpose of creating an opinion about current facts. The selected corpus has specificities showing the appealing potential of humorous discourse in the media that, despite aggressive, has the ability of captivating due to its performance through language with like and dislike pathos discursive intents. This less conventional kind of humor in our society has drawn our interest and could justify the present study